Study On The Availability Of Public Green Open Space Using Geographic Information System Data On Public Green Open Space In The City Of Tebing Tinggi - Bella Savitri, Chairuni; Badaruddin, Badaruddin; Charloq, Charloq (Publisher Cv. Inara, 2023)
Based on Spatial Planning Law No. 26 of 2007 concerning Spatial Planning, Article 29 states that the proportion of public green open space is 20% of the city area. In Tebing Tinggi City, based on the 2013-2033 RTRW of Tebing Tinggi City, it is stated that Public RTH covers an area of ??approximately 72.49 Ha or 1.89% of the city area, which means it is not in accordance with the mandate of Spatial Planning Law No. 26 2007 concerning Spatial Planning. This research was conducted to assess the availability of existing public green open space in Tebing Tinggi City based on image interpretation techniques, spatial distribution, the area of ??existing public green open space, the service radius of existing public green open space, and the suitability of existing public green open space land. This type of research uses quantitative research and uses spatial analysis techniques. The results identified as many as 60 public green open spaces in Tebing Tinggi City with an accuracy score of 86.36%, which means that the interpretation is considered correct because the spatial distribution pattern of public green open spaces in Tebing Tinggi City is random because the distribution of public green open spaces is not evenly distributed in all sub-districts in Tebing Tinggi City. From the results of the spatial distribution pattern, digitization was then carried out with the result that the total public open space area was 105.27 Ha, which was dominated by the burial area of ??59.67 Ha or 57.07%. Then, based on each area of ??green open space obtained, a topological classification of public green open space is carried out, consisting of 7 typologies of green open space, namely City Forest, City Park, District Park, Village Park, RW Park, RT Park, Cemetery and Green Belt, which is then analyzed. Service radius. As a result, it is known that the City of Tebing Tinggi has not been served optimally by public green open space because there is not yet one type of public green open space typology that is capable of serving the city of Tebing Tinggi based on buffer analysis carried out using ArcGis. The only public green open space whose service radius almost covers the city of Tebing Tinggi is the cemetery whose existing existence is capable of serving 99.19 percent of the area of ??the city of Tebing Tinggi. Finally, a land suitability analysis was carried out between the existing public green open space and the Tebing Tinggi City RTRW for 2013-2033 which resulted in land suitability of 79.92%. Meanwhile, the remaining 20.08% was designated for areas that were not public green open space.